2014
DOI: 10.3892/ol.2014.1857
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1 haplotypes are associated with P-gp activity and affect a major molecular response in chronic myeloid leukemia patients treated with a standard dose of imatinib

Abstract: Despite the high efficacy of imatinib mesylate (IM) treatment for chronic myeloid leukemia (CML) patients, some individuals develop resistance due to impaired bioavailability. It has been previously demonstrated that the haplotypes for ATP-binding cassette subfamily B member 1 (ABCB1)with c.1236C>T, c.3435C>T and c.2677G>T/A polymorphisms markedly affect the secondary structure of ABCB1 mRNA and its activity. These modifications may affect efflux transporter activity and response to treatment with IM. The aim … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 46 publications
2
21
2
Order By: Relevance
“…European Leukemia Net defines CMR as BCR-ABL mRNA transcripts undetectable by qRT-PCR and/or nested PCR in two consecutive high-quality samples with sensitivity (Cross et al, 2012). Our results showed that MDR1 rs1128503, rs1045642, and rs2032582 polymorphisms had no significant association with the MMR and CMR in CML patients that received the IM therapy, which is contrary to a few previous studies that showed genetic variations in MDR1 influenced response to IM in CML patients (Seong et al, 2013;Vivona et al, 2014). This might be attributed to the obscure definition of CML and the doses of IM in the included studies.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…European Leukemia Net defines CMR as BCR-ABL mRNA transcripts undetectable by qRT-PCR and/or nested PCR in two consecutive high-quality samples with sensitivity (Cross et al, 2012). Our results showed that MDR1 rs1128503, rs1045642, and rs2032582 polymorphisms had no significant association with the MMR and CMR in CML patients that received the IM therapy, which is contrary to a few previous studies that showed genetic variations in MDR1 influenced response to IM in CML patients (Seong et al, 2013;Vivona et al, 2014). This might be attributed to the obscure definition of CML and the doses of IM in the included studies.…”
Section: Discussioncontrasting
confidence: 96%
“…SNPs have the potential to affect the expression and function of the P-gp, could also influence the efficiency of absorption or elimination of IM and could explain at least in part variable responses to this drug (Elghannam et al, 2014). Vivona et al (2014) revealed a significant association between MDR1 haplotypes and P-gp activity in CML patients, which further supports our result. This result was also consistent with the result of study reported by B Zu et al (2014), which suggested that MDR1 rs1128503 polymorphism was associated with the increasing risk of IM resistance in Asian CML patients.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations